Increasing the performance of techniques of rowing on yalks with a roll-up system based on kinematic analysis and computer simulation - Sheichenko T.A. ,; Ponomarev G.N. ,; Sheichenko D.R. , (Theory and Practice of Physical Culture, 2024)
Objective of the study was to identify, on the basis of kinematic analysis and modeling, the effectiveness of using the developed rowing technique on yawls with a rolling system in the training process. Methods and structure of the study. The work used methods of kinematic analysis and modeling using electronic digital models, processing of experimental results using methods of mathematical statistics. Athletes specializing in rowing at YaL-6 (n=32) took part in the pedagogical experiment (from April 2022 to October 2023). Results and conclusions. It was found that kinematic analysis of digital layouts makes it possible to increase rowing efficiency on YaL 6. Changes made to the rowing technique based on kinematic analysis provide a statistically significant increase in rowing efficiency on YaL 6 (p≤0,05).